Mobile ASP.NET MVC 5 - Sowell, Eric.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Mobile ASP.NET MVC 5 will take you step-by-step through the process of developing fluid content that adapts its layout to the client device using HTML, JavaScript and CSS, and responsive web design. This book introduces server-side techniques that allow you to show different content to different devices and make the most of their strengths and capabilities. Mobile ASP.NET MVC 5 includes a wide range of techniques, tips, and guidelines for dealing with some of the challenges of mobile web development, such as browser incompatibilities, varying device performance, and targeting older devices. You$1 (Bll learn to: Use responsive principles to build apps that display and perform well on a range of mobile devices. Leverage your server-side code to customize what you serve to the client, depending on its capabilities. Build an ASP.NET MVC custom view engine, use display modes effectively, and create reusable mobile components with custom HTML helpers. Make the most of new capabilities offered on some devices by interacting with native APIs. By the end of Mobile ASP.NET MVC 5, you should feel confident building web apps that successfully target anything from an iOS or Android device to a feature phone or an older mobile browser. Along the way, you'll learn about the modern mobile web landscape and how to choose the approaches that are right for you, depending on your target audience. This book is for the ASP.NET developer who knows how ASP.NET MVC works and is eager to learn how to use it for building mobile websites.s
Keywords: Computer science; Computer Science; Computer Science, general